2013
DOI: 10.1111/jvim.12201
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography Guided Patent Ductus Arteriosus Occlusion with a Duct Occluder

Abstract: Background: Angiography and fluoroscopy are the standard methods to guide transcatheter occlusion of patent ductus arteriosus (PDA). The use of iodinated contrast agents and radiation exposure pose risks of animals and staff.Objectives: To assess feasibility of transesophageal echocardiography (TEE) for device size selection and procedure monitoring for PDA occlusion with a duct occluder (DO) without the use of angiography.Animals: Eighty client-owned dogs with left-to-right PDA. Methods: Prospective study. Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 17 publications
1
30
1
Order By: Relevance
“…Although we have shown previously that TTE can be used during transcatheter PDA occlusion with ACDO, TEE overcame the problem of inadequate image quality in a minority of dogs in which ductal morphology and ACDO positioning could not be assessed sufficiently for safe deployment . In addition, TEE permitted multiplane imaging to best characterize the anatomy and size of the PDA …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we have shown previously that TTE can be used during transcatheter PDA occlusion with ACDO, TEE overcame the problem of inadequate image quality in a minority of dogs in which ductal morphology and ACDO positioning could not be assessed sufficiently for safe deployment . In addition, TEE permitted multiplane imaging to best characterize the anatomy and size of the PDA …”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiography has proven useful in evaluating PDA morphology thereby guiding appropriate device selection, and TEE in combination with fluoroscopy, has been used to guide transcatheter coil embolization and for deployment of Amplatz Canine Ductal Occluder (ACDO) in dogs . Recently, investigators examined the combined use of TEE and fluoroscopy to guide PDA occlusion using ACDO in 80 dogs . Using 2 screens (1 each for TEE and fluoroscopic imaging) to simultaneously monitor the procedures, they found that TEE provided complete monitoring of the entire procedure in 73/80 (91%) dogs .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the standard procedure is performed under fluoroscopic guidance. However, PDA occlusion under transesophageal echocardiography guidance has also been proposed (15,20). The percutaneous procedure is usually carried out via the transarterial femoral artery approach (14); otherwise, carotid artery (13) or brachial artery (18) is recommended.…”
Section: Discussionmentioning
confidence: 99%